Acute exposure guideline levels for selected airborne chemicals. (Acute exposure guideline levels for selected airborne chemicals., 2010)
This book is the ninth volume in the series Acute Exposure Guideline Levels for Selected Airborne Chemicals, and reviews AEGLs for bromine, ethylene oxide, furan, hydrogen sulfide, propylene oxide, and xylenes.